1985
DOI: 10.1021/ac00285a020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sulfur dioxide, nitrogen oxides, and carbon dioxide in emissions from electric utility plants by alkaline permanganate sampling and ion chromatography

Abstract: A manual 24-h Integrated method for determining S02, NOx, and C02 In emissions from electric utility plants was developed and field tested downstream from an S02 control system. Samples were collected In alkaline potassium permanganate solution contained In restricted-orifice Implngers. S02 Is oxidized to S042" and S2Oe2", and NOx (NO + N02) Is oxidized to N03"; C02 Is converted to C032". Samples were analyzed by Ion chromatography. The method showed 100% collection efficiency for all three pollutants at a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Margeson et al 16 demonstrated that a 0.25 M KMnO 4 and 0.5 M NaOH solution can consistently collect 100% of NO x passed through when using this solution for NO x concentration analysis in power plant stacks. Margeson et al 21 later adjusted the method to use a 0.25 M KMnO 4 and 1.0 M NaOH solution to collect additional acidic gases in solution, but when tested for isotopic analysis of NO x , this solution had a higher NO 3 − background and showed greater variability in isotopic composition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Margeson et al 16 demonstrated that a 0.25 M KMnO 4 and 0.5 M NaOH solution can consistently collect 100% of NO x passed through when using this solution for NO x concentration analysis in power plant stacks. Margeson et al 21 later adjusted the method to use a 0.25 M KMnO 4 and 1.0 M NaOH solution to collect additional acidic gases in solution, but when tested for isotopic analysis of NO x , this solution had a higher NO 3 − background and showed greater variability in isotopic composition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…System calibrations were carried out before, during, and after a sample run, as described earlier. 2 No significant calibration drift was observed. SO 2 and CO2 concentrations were recorded on strip charts and manually reduced to 24-h averages by taking the arithmetic mean of concentrations recorded at 15-min intervals (~95 data points).…”
Section: Reference Measurementsmentioning
confidence: 96%
“…In the first test, sample conditioning was essentially the same as that reported earlier. 2 Samples were extracted with a borosilicate glass probe that was followed by the sample conditioning system and a manifold that served the monitors. A plug of heated quartz wool was used near the probe inlet to remove particulate matter.…”
Section: Reference Measurementsmentioning
confidence: 99%
See 2 more Smart Citations